ANALISIS KEBUTUHAN MATERI KIMIA UNTUK SISWA SMK KOMPETENSI KEAHLIAN ANALISIS PENGUJIAN LABORATORIUM - Ika Nurhayati, - (2021)
Penelitian ini dilatarbelakangi oleh kurang tersedianya bahan ajar kimia yang relevan untuk siswa SMK kompetensi keahlian Analisis Pengujian Laboratorium (APL). Materi kimia yang terdapat dalam bahan ajar kimia SMK masih bersifat umum belum dikaitkan dengan materi kejuruan yang terdapat di SMK, sehingga fungsi mata pelajaran kimia sebagai mata pelajaran adaptif belum terpenuhi. Penelitian ini bertujuan untuk memperoleh outline bahan ajar kimia yang berisi ruang lingkup materi kimia yang dibutuhkan oleh siswa SMK kompetensi keahlian APL. Outline bahan ajar kimia ini dapat dijadikan acuan untuk mengembangkan bahan ajar kimia di SMK kompetensi keahlian APL. Desain penelitian yang digunakan adalah Design and Development (D&D) dengan metode deskriptif evaluatif. Partisipan dalam penelitian ini terdiri dari dua ahli pendidikan kimia, tiga guru kimia SMK, dan empat guru kejuruan APL. Data diperoleh melalui wawancara terhadap guru kimia dan guru kejuruan APL, analisis pemetaan materi kimia, dan analisis ruang lingkup materi kimia di SMK kompetensi keahlian APL. Teknik analisis data dilakukan secara kualitatif. Hasil penelitian menunjukkan bahwa: 1) materi kimia adaptif yang dipelajari masih terlalu umum untuk konteks kejuruan sehingga tidak terdapat kesesuaian antara materi kimia yang dipelajari dengan materi kimia yang dibutuhkan untuk menunjang kompetensi siswa dalam mempelajari materi kejuruannya di APL; 2) dari analisis pemetaan materi kimia diperoleh tiga belas materi kimia yang relevan dan dibutuhkan untuk menunjang materi kejuruan yang terdapat di SMK kompetensi keahlian APL; 3) ruang lingkup materi kimia dibuat dalam bentuk outline bahan ajar yang ditentukan berdasarkan hasil analisis pemetaan materi kimia dengan memperhatikan materi kimia prasyarat sehingga diperoleh rincian materi kimia yang spesifik untuk siswa SMK kompetensi keahlian APL. The background of the research initiated due to the lack of availability of relevant chemistry teaching materials for students of Vocational High School (VHS) expertise competency of Laboratory Testing Analysis. The chemical materials contained in the chemistry teaching materials of VHS is still general and has not been linked to vocational materials in VHS, so that the function of chemistry subject as adaptive subject has not been fulfilled. This study aims to obtain an outline of chemistry teaching materials which involves the scope of chemistry materials which are needed by students of VHS expertise competency of Laboratory Testing Analysis. Furthermore, the outline of these chemistry teaching materials can be used as a reference for developing chemistry teaching materials in VHS expertise competency of Laboratory Testing Analysis. The research design used is Design and Development (D&D) with a descriptive evaluative method. The participants in this study consisted of two chemistry education experts, three vocational chemistry teachers, and four vocational Laboratory Testing Analysis teachers. The data were obtained through interviews with vocational chemistry teachers and vocational Laboratory Testing Analysis teachers, analysis of chemistry materials mapping, and analysis of the of chemistry scope in VHS expertise competency of Laboratory Testing Analysis. The data analysis technique was conducted qualitatively. The results of the research show that: 1) the adaptive chemistry materials which is learned is still too general for a vocational context so that there was no correlation between the chemistry materials being studied and the chemistry materials needed to support students in learning their vocational materials in Laboratory Testing Analysis; 2) from the analysis of the mapping of chemical materials, there are thirteen chemistry materials which are relevant and needed to support vocational materials contained in VHS expertise competency of Laboratory Testing Analysis; 3) the scope of the chemistry materials is determined based on the results of the chemical mapping analysis by taking into account the prerequisite chemistry so that specific chemistry materials details are obtained for vocational students Laboratory Testing Analysis expertise competency. Key words: Need Analysis, Teaching Materials, Outline of Teaching Materials, Chemical Materials, Vocational Materials, Laboratory Testing Analysis.